Pituitary gonadotroph-specific patterns of gene expression and hormone secretion. (October 2022) - Constantin, Stephanie; Bjelobaba, Ivana; Stojilkovic, Stanko S.
Abstract: Pituitary gonadotrophs play a key role in reproductive functions by secreting luteinizing hormone (LH) and follicle-stimulating hormone (FSH). The LH secretory activity of gonadotroph is controlled by hypothalamic gonadotropin-releasing hormone (GnRH) via GnRH receptors and is accompanied by only minor effects on high basal Lhb gene expression. The secretory profiles of GnRH and LH are highly synchronized, with the latter reflecting a depletion of prestored LH in secretory vesicles by regulated exocytosis. In contrast, FSH is predominantly released by constitutive exocytosis, and secretory activity reflects the kinetics of Fshb gene expression controlled by GnRH, activin, and inhibin. Here is a review of recent data to improve the understanding of multiple patterns of gonadotroph gene expression and hormone secretion.